Uspešnost sinhroniziranja nekaterih animiranih filmov z jezikoslovčevega vidika - Krajnc Ivič, Mira (Slavia Centralis, 2020)
A Linguistic Approach to the Success of Synchronization in Animated Films The paper establishes significant differences between subtitles, which mostly observe the Slovene linguistic code and synchronization, which recreates the spoken word as it is used in everyday situations with characteristics typical of spoken discourse; thus, marginal and excessive sociolects and unfinished syntactic structures, discourse markers, changes in word order etc. are included. Synchronization is more expressive than subtitles because of its actualization of idioms, text and context allusions known to Slovenian recipients.